2012
DOI: 10.1371/journal.pone.0047513
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling Identified Methylerythritol Cyclodiphosphate Efflux as a Limiting Step in Microbial Isoprenoid Production

Abstract: Isoprenoids are natural products that are all derived from isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP). These precursors are synthesized either by the mevalonate (MVA) pathway or the 1-Deoxy-D-Xylulose 5-Phosphate (DXP) pathway. Metabolic engineering of microbes has enabled overproduction of various isoprenoid products from the DXP pathway including lycopene, artemisinic acid, taxadiene and levopimaradiene. To date, there is no method to accurately measure all the DXP metabolic intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 31 publications
4
91
2
Order By: Relevance
“…There are, however, situations where this approach may be limited, as in the cases where (i) a single host cell cannot provide an optimal environment for the functioning of all pathway enzymes, (ii) biosynthetic efficiency is reduced due to overwhelming metabolic stress from the overexpression of long and complex pathways (3,4), or (iii) pathway intermediates are secreted yielding undesired byproducts and reducing substrate utilization (5,6). The above limitations can potentially be overcome through the use of rationally designed microbial coculture systems.…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…There are, however, situations where this approach may be limited, as in the cases where (i) a single host cell cannot provide an optimal environment for the functioning of all pathway enzymes, (ii) biosynthetic efficiency is reduced due to overwhelming metabolic stress from the overexpression of long and complex pathways (3,4), or (iii) pathway intermediates are secreted yielding undesired byproducts and reducing substrate utilization (5,6). The above limitations can potentially be overcome through the use of rationally designed microbial coculture systems.…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…Our calculations of MEcDP partitioning between the plastid and nonplastid pools indicate that this diversion occurs in DXS-overexpressing plants, but not in wild-type plants under our growing conditions. DXS overexpression may inadvertently trigger a natural efflux process involved in stress signaling that occurs under certain environmental conditions (Xiao et al, 2012;Zhou et al, 2012).…”
Section: The High Fcc Of Dxs Indicates Its Role In Controlling the Mementioning
confidence: 99%
“…MEcDP efflux was recently described for an Escherichia coli strain overexpressing DXS (Zhou et al, 2012), possibly as a response to oxidative stress. MEcDP diversion may also result from pathogen attack as part of a stress response mediated by salicylic acid (Gil et al, 2005).…”
Section: The Second Pool Of Mecdp May Also Be Present In Wildtype Plantsmentioning
confidence: 99%
“…Previous report (Zhou et al, 2012) showed that overexpression of dxs, idi and ispDF could lead to over-production and accumulation of MECPP in cell to outflow into the broth that is toxic to MEP pathway, which further decreased the lycopene production. The same situation may also appear in the current study where the outflow of MECPP produced by overexpression of genes dxs, idi and ispDF reduced toxic effect to MEP pathway, thus increased transcriptional levels of dxs and idi genes in strain YSS8.…”
Section: Discussionmentioning
confidence: 94%
“…Overexpression of genes dxr (Lv et al, 2016), ispDF Yuan et al, 2006), ispG (Liu et al, 2014) and ispA (Han et al, 2016) were able to enhance terpenoids production. On the contrary, other studies have shown that overexpression of dxr coupled with dxs produced a similar isoprene level when compared with the dxs overproduction strain (Xue and Ahring, 2011), and overexpression of ispDF together with dxs and idi resulted in decrease in terpenoids production (Zhou et al, 2012). Meanwhile, genes ispH, ispE and ispA have not been overexpressed in combination with dxs and idi genes of MEP pathway in the production of terpenoids in E. coli.…”
Section: Introductionmentioning
confidence: 85%